Personalized nutrition - Appert, Linnea (2018)
Diet related diseases is an increasing problem, and new approaches are needed to prevent, motivate and treat affected individuals. Evidence show inter-individual nu- trient requirements and differences in response to dietary manipulations. National dietary guidelines are generally one set of advice to the entire healthy population. While specific dietary guidelines for metabolic diseases exist, individualized pre- ventive measures for people at risk is sought after. To meet the demands of individ- ualization, the field of personalized nutrition (PN) is emerging which aims to create and maintain healthy dietary habits for all phenotypes without regard for their health status. This literature review examines areas of development and investigates dif- ferent levels of personalization by employing information from different biological disciplines. By analyzing nutritional metabolites in plasma i.e nutritional metabo- lomics, it makes it possible to study the interactions between these and gut microbi- ota, nutrigenomics and phenotypic metabolites. By forming clusters of distinct mo- lecular phenotypes i.e. metabotypes, it may be possible to deliver targeted dietary advice (DA) to the groups in the population with similar phenotypic characteristics through the use of metabolomics. PN has the potential to be an important tool for achieving healthy dietary habits, e.g. by predicting and identifying responders to certain dietary interventions which achieve a low postprandial glycemic response. However, current evidence does not support the eventual health benefits with in- cluding individual information in DA to the population. Integrating omics technol- ogies and applying technical solutions e.g internet, for the distribution of DA has shown to have strong potential in delivering PN.